Delineating soil moisture dynamics as affected by tillage in wheat, Rice and establishment methods of rice during intervening period (Journal of Applied and Natural Science, 2015)
Intervening cropping period perhaps the most ignored period, which could be exploited for cultivating the intervening crops which further add to the soil, crop and water productivity and finally livelihood of the farmers of the region. The present investigation was carried out after rice- 2014, to monitor the residual effect of different tillage (wheat), establishment methods and tillage (rice) on the fluctuating behaviour of the soil moisture during intervening period. Our findings suggested that CTW-DSRZT (conventionally tilled wheat and zero till direct seeded rice) plots conserved more moisture than ZTW-DSRZT (zero till wheat and zero till direct seeded rice) plots an exception of CTWDSRCT plots which were almost equally effective in conserving the soil moisture. On an average, soil matric tension (SMT) was reported to be 36% higher in CTWDSRZT than CTWDSRP plots at 10cm soil surface. Further, ZTW-DSRZT plots on an average dried 8% faster than ZTW-DSRP plots. At 20cm, DSRZT plots dried 3% faster than its allied plots while at 30cm depth, in DSRP plots, SMT values increased 12% and 11% higher under CTW block and ZTW blocks, respectively than its allied plots. SMT readings in all the ZTW plots on an average increased at much more faster rates (24%) than CTW plots. The ZT plots had 1.4% higher water depths than the CT plots. Evaporation losses pragmatic to be higher (17.2% and 7.3%) in ZTW-DSRZT plots as compared to the ZTW-DSRCT and CTW-DSRCT plots which might improve declining crops and water productivity in the region.